Detection methods and biological treatment of typical organic compounds in tail water of chemical/pharmaceutical industrial parks - YANG Lei; FU Ruotong; JIN Wenhui; FU Shiying; SHAO Zhen; WANG Xueting; CHEN Chuan* (能源环境保护)
In order to meet the demand for the identification and detection of high-risk environmental pollutants in industrial park tail water, this paper adopted the gas chromatography-mass spectrometry (GC-MS) method to achieve the rapid qualitative analysis of alkanes, olefins, benzenes, ketones, alcohols, esters, acids, and other organics in the tail water of chemical/ pharmaceutical industrial parks. Based on the production process and water quality research and analysis of key enterprises within the industrial park, typical organic compounds, including 3-hexanol, 3-hexanone, methyl 3-(3,5-di-tertbutyl-4-hydroxyphenyl) propionate, and 4-bromo-2,6-di-tert-butylphenol were selected. A high-performance liquid chromatography (HPLC) method was established to analyze these compounds in the tail water achieving recoveries of 80% to 97% and the average recoveries of 87% to 95%. Furthermore aerobic and anaerobic biological sequential batch experiments were conducted to verify the biodegradation effect of these typical organics. The results showed that aerobic treatment was more effective than anaerobic treatment, with concentration removal rates ranging from 48.0% to 88.8%, COD removal rates from 70.8% to 99.9%, and average TOC removal rates from 54.7% to 79.5%. These findings provide theoretical and technological support for the further studies on advanced treatment technology or the upgrading and transformation of processes for industrial wastewater.